COPING MECHANISM OF BREAST CANCER PATIENTS UNDERGOING CHEMOTHERAPY DURING THE COVID-19 PANDEMIC - Mutia Nadra Maulida; Putri Widita Muharyani; Eka Yulia Fitri; Karolin Adhisty (Conferences of Medical Sciences Dies Natalis, 2021)
Cancer is one of the most common non-communicable and chronic diseases in the world, one of them is breast cancer. Breast cancer is a disorder in the growth of normal breast cells which is characterized by abnormal cells arising from normal cells that can infiltrate lymph tissue and blood vessels. This will have a major impact on patients undergoing chemotherapy and their families, especially during the COVID-19 pandemic. Not only physically but also psychologically, economically and in other aspects of life, which certainly affect the coping mechanisms of patients and families. One of the support efforts that can be provided by nurses as educators is the intensification of health education activities through community service activities in the form of counseling and coaching to improve the coping mechanisms of breast cancer patients.